Utilization of Digital Media to Restore Reading Interest for University Students - Sumiati Sumiati; Nurhidaya M; Mumtahanah Mumtahanah; Ratna M; Shilsilah Nurfadilah Asmi (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this research is to use digital media to rekindle a love of reading among students at the Faculty of Islamic Religion at Unismuh Makassar. Studying how people read with digital media is crucial, as such platforms are now an integral part of most people's lives, and notably those of the digital native millennial generation. Digital media is a type of digital content that can be played by digital media players. Students' behavior and routines have been impacted by the prevalence of digital technology in their lives. Reading books is one activity that has experienced significant change among the younger population, particularly among students. Most students today choose to use search engines on their mobile devices to find the information they need for class. The purpose of this study was to collect comprehensive data on how to rekindle students' love of reading through the creative use of existing digital media. A quantitative strategy was employed in the study's analysis. Students fill out a survey to help gather information. Frequency analysis is used to determine how frequently each answer was provided in the collected data. Parametric analysis is supplemented with descriptive analysis to provide light on what may be done to rekindle a love of reading among Unismuh Makassar students. The findings demonstrate a daily digital media consumption rise, from three to twelve hours on average.